2014
DOI: 10.1603/ec13542
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between the Entomopathogenic Fungi <I>Beauveria bassiana</I> (Ascomycota: Hypocreales) and the Aphid Parasitoid <I>Diaeretiella rapae</I> (Hymenoptera: Braconidae) on <I>Myzus persicae</I> (Hemiptera: Aphididae)

Abstract: The interactions between the entomopathogenic fungus Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Ascomycota: Hypocreales) and the aphid parasitoid Diaeretiella rapae McIntoch (Hymenoptera: Braconidae) were evaluated under laboratory conditions. Nymphs of Myzus persicae Sulzer (Hemiptera: Aphididae) were first exposed to parasitoid females for 24 h and then 0, 24, and 48 h afterwards sprayed with a solution of B. bassiana. Likewise, aphids were also sprayed with B. bassiana and then exposed to parasitoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Moreover, EPF can be used in combination with the parasitoids and predators, as biological control agents, for controlling the aphids. This method requires an effective time management in order to prevent the antagonistic interactions (Martins et al 2014 andSeiedy et al 2015).…”
mentioning
confidence: 99%
“…Moreover, EPF can be used in combination with the parasitoids and predators, as biological control agents, for controlling the aphids. This method requires an effective time management in order to prevent the antagonistic interactions (Martins et al 2014 andSeiedy et al 2015).…”
mentioning
confidence: 99%
“…This effect of the time interval between parasitization and fungal infection is well documented (e.g., Rashki et al [ 29 ], Aqueel and Leather [ 30 ], Askary and Brodeur [ 64 ]). Martins et al [ 39 ], reported a lower level of parasitism of Myzus persicae Sulzer (Homoptera: Aphididae) by Diaeretiella rapae Maclntosh (Hymenoptera: Braconidae) at 0 and 24 h before inoculation with B . bassiana.…”
Section: Discussionmentioning
confidence: 99%
“…They found that IGP was modulated in a dose- and age-dependent manner, and the effect of B. bassiana was stronger when the host was recently parasitized by T. triozae . According to Furlong and Pell [ 24 ], entomopathogenic fungal infections can compromise the development of pre-existing parasitoids in hosts, and several studies determined the susceptibility of adult parasitoids to various EPFs, and the interactions occurring within the host insects [ 27 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies about interactions between entomopathogenic fungi and other natural enemies (parasitoids and predators) have been performed worldwide (Roy et al 2006;Ormond et al 2011;Martins et al 2014;Bayissa et al 2016). However, there is very little information about interactions with other natural enemies in Coccinellidae species in general and E. connexa in particular.…”
Section: Discussionmentioning
confidence: 99%